2016
DOI: 10.1136/bmjspcare-2015-001064
|View full text |Cite
|
Sign up to set email alerts
|

Psychological processes of suffering of palliative care patients in Malaysia: a thematic analysis

Abstract: Although suffering in palliative care has received increasing attention over the past decade, the psychological processes that underpin suffering remain relatively unexplored.ObjectiveTo understand the psychological processes involved in the experiencing of suffering at the end phase of life.MethodsSemistructured interviews were conducted with 20 palliative care inpatients from an academic medical centre in Kuala Lumpur, Malaysia. The transcripts were thematically analysed with NVIVO9.Results5 themes of psycho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…In some cases, hastening death is seen as being the only means left to ameliorate the suffering of the patient. Contrary to accepted notions of suffering being physical and largely the product of pain, Tan et al 27 revealed from a study within the Chinese community in Malaysia that patients and families reported no less than 10 forms of suffering. Examples of such suffering, where standard treatment modalities do not help, include emotional, cognitive and spiritual suffering.…”
Section: Intention Behind Wd/wh Treatment In the Terminal Discharge Smentioning
confidence: 87%
See 1 more Smart Citation
“…In some cases, hastening death is seen as being the only means left to ameliorate the suffering of the patient. Contrary to accepted notions of suffering being physical and largely the product of pain, Tan et al 27 revealed from a study within the Chinese community in Malaysia that patients and families reported no less than 10 forms of suffering. Examples of such suffering, where standard treatment modalities do not help, include emotional, cognitive and spiritual suffering.…”
Section: Intention Behind Wd/wh Treatment In the Terminal Discharge Smentioning
confidence: 87%
“…Within the local context, this stems from patient’s having to witness the suffering of family members as a result of the patient’s own distress. 27 Being a burden to the family is also seen as a major regret of patients and may feed into this duty. Misinterpretation of Confucian ethics that place primacy upon the interests of the family over those of the individual particularly when physical, financial and practical costs of care become the primary responsibility of the family may strengthen a duty to die or at least to cease with efforts to prolong life.…”
Section: Intention Behind Wd/wh Treatment In the Terminal Discharge Smentioning
confidence: 99%
“…In this study, focusing on reducing patient's pain is one of the main aspects of paying attention to patient's needs, and care-providers tried to reduce the pain by inducing a sense of worthiness in patients. The results of other studies have also considered the attempt to reduce patient's physical, mental and psychological pain as a principle of paying attention to the patient's needs; and to do so, they have used different strategies such as music therapy, yoga, and psychological support to reduce the patient's pain [52][53][54][55][56]. In addition to emphasizing the consideration of patients' physical and mental aspects in reducing patients' pain, the results of this study have also highlighted the significance of reducing the pressure imposed on caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…The psychological processes of suffering in palliative care patients involve perceptions, cognitive appraisals, hope and the struggles with acceptance, emotions and clinging (Tan et al, 2019). Mindfulness can transform suffering by changing what the mind is processing (switching attention from the psychological processes of suffering to another object of attention), changing how the mind is processing it (changing the way how patients relate with their sources of suffering), and changing the view of what is being processed (seeing the psychological processes as dynamically unfolding impersonal processes without identifying them as ‘I’, ‘me’ or ‘mine’) (Teasdale & Chaskalson, 2011).…”
Section: Introductionmentioning
confidence: 99%